The New Frontier of Host-Directed Therapies for Mycobacterium avium Complex - Crilly, Nathan P.; Ayeh, Samuel K.; Karakousis, Petros C. (Frontiers in Immunology, 2021)
Mycobacterium avium complex (MAC) is an increasingly important cause of morbidity and mortality, and is responsible for pulmonary infection in patients with underlying lung disease and disseminated disease in patients with AIDS. MAC has evolved various virulence strategies to subvert immune responses and persist in the infected host. Current treatment for MAC is challenging, requiring a combination of multiple antibiotics given over a long time period (for at least 12 months after negative sputum culture conversion). Moreover, even after eradication of infection, many patients are left with residual lung dysfunction. In order to address similar challenges facing the management of patients with tuberculosis, recent attention has focused on the development of novel adjunctive, host-directed therapies (HDTs), with the goal of accelerating the clearance of mycobacteria by immune defenses and reducing or reversing mycobacterial-induced lung damage. In this review, we will summarize the evidence supporting specific adjunctive, HDTs for MAC, with a focus on the repurposing of existing immune-modulatory agents targeting a variety of different cellular pathways. We also highlight areas meriting further investigation.